2019
DOI: 10.1093/ajcn/nqz001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a diet based on inulin-rich vegetables on gut health and nutritional behavior in healthy humans

Abstract: Background Inulin-type fructans (ITFs) are a type of fermentable dietary fiber that can confer beneficial health effects through changes in the gut microbiota. However, their effect on gut sensitivity and nutritional behavior is a matter of debate. Objective We evaluated the impact of consuming ITF-rich vegetables daily on gut microbiota, gastro-intestinal symptoms, and food-related behavior in healthy individuals. Methods A single group-desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 51 publications
(60 reference statements)
7
85
1
Order By: Relevance
“…In fact it has been shown that two weeks of consuming vegetables rich in inulin-type fructans led to a 3.8-fold increase in the Bifidobacterium genus, and, at the species level, it induced an increase in B. longum subsp. longum and, to a lesser extent, B. pseudocatenulatum, B. bifidum and B. adolescentis [22]. These results confirm previous data, which showed that the consumption of Jerusalem artichoke (rich in inulin) was related to an increase in Bifidobacterium [39,40].…”
Section: Fructanssupporting
confidence: 90%
See 2 more Smart Citations
“…In fact it has been shown that two weeks of consuming vegetables rich in inulin-type fructans led to a 3.8-fold increase in the Bifidobacterium genus, and, at the species level, it induced an increase in B. longum subsp. longum and, to a lesser extent, B. pseudocatenulatum, B. bifidum and B. adolescentis [22]. These results confirm previous data, which showed that the consumption of Jerusalem artichoke (rich in inulin) was related to an increase in Bifidobacterium [39,40].…”
Section: Fructanssupporting
confidence: 90%
“…At the same time, dietary strategies, aimed to enhance the adherence to the Mediterranean diet, can be associated with health benefits. A regular consumption of fibers is conducive to the maintenance of the beneficial effects; indeed, in the study by Hiel et al [22], three weeks after the end of inulin-rich vegetables diet, the levels of Bifidobacterium genus and Clostridiales were shown to have returned to the previous levels.…”
Section: Prebiotics and Dietary Fibersmentioning
confidence: 98%
See 1 more Smart Citation
“…Soluble fiber supplementation resulted in increased biodiversity of gut microbiota composition, increased stability over time, and increased representation of Bifidobacteria [137,138]. Interestingly, an increase in fiber intake was also associated with decreased levels of Oxalobacteraceae, probably as a consequence of the reduced oxalate content of ingested foods [138].…”
Section: Fav Intake Legume Intake and Microbiotamentioning
confidence: 99%
“…To minimize confounding factors (especially various disease status), we used search terms "diet" AND "gut microbiome" AND "healthy adult" and included only clinical studies in healthy participants that have detailed diet and gut microbiome information (Supplemental Figure 2). We identi ed 16 eligible clinical studies [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] that included in total 771 subjects. Among them, 428 were females and 343 were males.…”
Section: Diet Could Potentially Affect the E Cacy Of Cancer Immunothementioning
confidence: 99%